Small-polaron transport in perovskite nickelates - M. Tyunina; M. Savinov; O. Pacherova; A. Dejneka (Scientific Reports, 2023)
Abstract Knowledge of the explicit mechanisms of charge transport is preeminent for a fundamental understanding of the metal-to-insulator transition in ABO3-type perovskite rare-earth nickelates and for potential applications of these technologically promising materials. Here we suggest that owing to intrinsic Jahn–Teller-driven carrier localization, small-polaron transport is innate in nickelates. We demonstrate experimental evidence for such transport by investigating AC conductivity over a broad range of temperatures and frequencies in epitaxial SmNiO3 films. We reveal the hopping mechanism of conductivity, Holstein-type activation energy for hopping, nonclassical relaxation behavior, and nonclassical consistency between activation and relaxation. By analyzing these observations, we validate small-polaron transport. We anticipate that our findings can lead to precise tailoring of the DC and AC conductivity in nickelates as requested for fruitful employment of these materials. We also believe that further investigations of self-trapped small polarons are essential for a comprehensive understanding of nickelates.